Influence of calendering on the properties of paper-derived alumina ceramics - Schlordt, Tobias; Dermeik, Benjamin; Beil, Veronika; Freihart, Matthias; Hofenauer, Andreas; Travitzky, Nahum; Greil, Peter (Ceramics International, 2013)
The effect of calendering of alumina loaded preceramic papers in a hard nip laboratory calender at various temperatures, line loads and times of nip passes on their green and sintered properties was investigated. The main objective was to achieve a maximum densification, which resulted in a maximum reduction of thickness of 45%, a green density of 80.5% of the theoretical density and a sintered density of 81% of the theoretical density. The ring-on-ring flexural strength of sintered specimen could be increased from 71±11 MPa to 138±33 MPa. The surface roughness of green samples could be diminished to a value for Ra of below 2 µm compared to an Ra of 13.2 µm for an uncalendered paper, whereas the Ra value of the sintered samples was much higher due to the burn-off of the cellulose fibers. Preceramic papers manufactured by the dynamic hand-sheet-forming process exhibit a fiber-orientation which causes anisotropic effects regarding the sintering shrinkage, the surface roughness and Young's modulus.
Keywords: Porosity; Surfaces; Mechanical properties; Preceramic paper